RELEVANSI PEMBENTUKAN DAYA ANAGATA NUSANTARA TERHADAP KEBIJAKAN EFISIENSI ANGGARAN PEMERINTAHAN KABINET MERAH PUTIH - Thoriq, Ahmad Reihan; Calista Azarine Larissa; Indira Nur Syahrani Makmur (Journal Social Sciences and Humanioran Review, 2024)
The Indonesian government established the Daya Anagata Nusantara Investment Management Agency (Danantara) as a sovereign wealth fund (SWF) to optimize state asset management and drive strategic investments. However, Danantara's formation raises questions about its alignment with the budget efficiency policy promoted by the Red and White Cabinet, particularly regarding its initial capital allocation of Rp1,000 trillion and the separation of potential losses from state finances under the revised State-Owned Enterprises Law (Article 3H Paragraph 2). This study aims to analyze Danantara's implications for budget efficiency and examine the regulatory framework separating its losses from state finances. The research employs a normative legal method through literature review. Findings indicate that Danantara's establishment may contradict budget efficiency principles due to the substantial funding allocation and risks of centralized asset management. Although Danantara's losses are legally not the state's responsibility, their impact on the national economy remains significant, especially in the event of a bailout. Additionally, lack of transparency in oversight Enterprises pose challenges. This study recommends reevaluating Danantara's policy to ensure compliance with good governance and budget efficiency principles.